Aspek Hukum dalam Transaksi Bisnis Digital serta Upaya Perlindungan Data Pribadi Konsumen dalam Era Teknologi - Hery Rahmawati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
In today's increasingly advanced digital era, technology usage is increasing, making personal identity crucial. Personal data plays a significant role because it directly relates to a person's self-esteem and freedom of expression. Without legal regulations governing the security of personal information, individuals could be harmed by data breaches. With the development of the digital era, which is increasingly integrated with big data, personal data is now a highly valuable commodity. This is understandable, as the growth of the digital economy has been proven to boost the overall economy. However, this development also brings various legal obstacles related to the legality of digital transactions and the security of individual data. This article aims to examine the relevant legal aspects of digital business activities in Indonesia and evaluate regulations on consumer personal data protection. Despite its high economic value, consumer identity data protection remains inadequate. Numerous cases of personal data breaches create significant concern. Therefore, it is important to recognize the forms of legal guarantees for consumers in cases of data breaches. This article aims to examine the relevant legal aspects of digital business transactions in Indonesia and analyze regulations on consumer personal data protection. This research applies a normative juridical method with a regulatory approach and a literature review. This research shows that while regulations such as the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law) are already in place, there are still weaknesses in their implementation that need to be harmonized and their supervision strengthened.